Restoration of Corticosteroid Sensitivity in Chronic Obstructive Pulmonary Disease by Inhibition of Mammalian Target of Rapamycin - Mitani, Akihisa; Ito, Kazuhiro; Vuppusetty, Chaitanya; Barnes, Peter J.; Mercado, Nicolas (American journal of respiratory and critical care medicine, 2016)
Corticosteroid resistance is a major barrier to the effective treatment of chronic obstructive pulmonary disease (COPD). Several molecular mechanisms have been proposed, such as activations of the phosphoinositide-3-kinase/Akt pathway and p38 mitogen-activated protein kinase. However, the mechanism for corticosteroid resistance is still not fully elucidated. To investigate the role of mammalian target of rapamycin (mTOR) in corticosteroid sensitivity in COPD. The corticosteroid sensitivity of peripheral blood mononuclear cells collected from patients with COPD, smokers, and nonsmoking control subjects, or of human monocytic U937 cells exposed to cigarette smoke extract (CSE), was quantified as the dexamethasone concentration required to achieve 30% inhibition of tumor necrosis factor-α-induced CXCL8 production in the presence or absence of the mTOR inhibitor rapamycin. mTOR activity was determined as the phosphorylation of p70 S6 kinase, using Western blotting. mTOR activity was increased in peripheral blood mononuclear cells from patients with COPD, and treatment with rapamycin inhibited this as well as restoring corticosteroid sensitivity. In U937 cells, CSE stimulated mTOR activity and c-Jun expression, but pretreatment with rapamycin inhibited both and also reversed CSE-induced corticosteroid insensitivity. mTOR inhibition by rapamycin restores corticosteroid sensitivity via inhibition of c-Jun expression, and thus mTOR is a potential novel therapeutic target for COPD.